An Efficient Algorithm for Web Page Change Detection - Goel, Srishti (My University, 2012)
Internet is being used for the exchange of information. People are using internet actively for exchange of information across the world resulting in uploading of information on web pages and updating new web pages very frequently. The contents of web page changes continuously & rapidly. Hence it becomes very difficult to observe the changes made in web pages and retrieve the original web pages. For efficient retrieval and monitoring the changes made in web pages and compare the difference between refreshed page and old page efficiently that too in minimum browsing time, an effective monitoring system for the web page change detection based on user profile is needed. The web page change detection system can be implemented by using various Tools or Algorithms. Various services are also available which can be used to detect the changes in a web page. In this thesis, a new algorithm for the structural as well as content change detection has been proposed and described. For better results tree has been designed for the corresponding web pages. The proposed change detection algorithm is based on assigning hash value to each leaf node and tag value to the non leaf nodes. Bottom up approach has been used for assignment. The level of each node has been used to find hash values and modification in a node. It has been shown with the help of suitable examples that the proposed algorithm extracts the changes very efficiently from the various web pages.
Keywords: Web Page Change Detection